23. Effects of visual paired associative stimulation on visual evoked potentials in healthy volunteers. Issue 12 (December 2017) - Ranieri, F.; Coppola, G.; Musumeci, G.; Capone, F.; Di Pino, G.; Parisi, V.; Di Lazzaro, V.
Abstract : Associative stimulation of peripheral afferents paired with low-frequency transcranial magnetic stimulation (LF-TMS) over the motor area (PAS) at an interstimulus interval (ISI) slightly shorter or longer than the time needed for the afferent inputs to reach the cerebral cortex, can decrease or increase the excitability of the motor system. None has proven whether the same time-dependent plasticity rules may also be valid for the visual system. In 12 healthy subjects, we performed a visual PAS (vPAS) protocol by coupling 90 black-and-white checkerboard reversals with LF-TMS pulses over the occipital cortex at 4 ISIs in separate sessions chosen by subtracting or adding 25/50 ms to the visual evoked potential (VEP) P1 latency. We recorded VEPs (600 sweeps) before, after, and 10-min later each vPAS session. VEPs were partitioned in 6 blocks of 100 sweeps. We analyzed VEP N1-P1 first amplitude and delayed habituation. VEP amplitude of the first block was reduced immediately after PAS+25, while it remained unchanged after the other vPAS protocols. Delayed VEP habituation significantly increased after PAS−25, and decreased after PAS+25. Associative bidirectional synaptic plasticity is not confined to the corticomotor system, but can also be a feature of the visual system.